2022
DOI: 10.1596/1813-9450-10136
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Household Dynamics and Attitudes toward Vaccines: Experimental and Survey Evidence from Zambia

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Our data are consistent with findings from a study in Zambia that assessed the intra-household dynamics and attitudes toward COVID-19 vaccines and found that the likelihood an individual would be willing to get vaccinated was around 62 percentage points higher when other household members were also willing to get vaccinated. 16 This supports the notion that social contagion -that people's decisions are influenced by the behavior of others around them 17 influences COVID-19 vaccine acceptance and emphasizes the importance of social norms for vaccine acceptance in rural Liberia. It also suggests that a target for vaccine hesitancy interventions may be discordant households where changing the pro-vaccine attitude of one household member could influence other members of their home.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our data are consistent with findings from a study in Zambia that assessed the intra-household dynamics and attitudes toward COVID-19 vaccines and found that the likelihood an individual would be willing to get vaccinated was around 62 percentage points higher when other household members were also willing to get vaccinated. 16 This supports the notion that social contagion -that people's decisions are influenced by the behavior of others around them 17 influences COVID-19 vaccine acceptance and emphasizes the importance of social norms for vaccine acceptance in rural Liberia. It also suggests that a target for vaccine hesitancy interventions may be discordant households where changing the pro-vaccine attitude of one household member could influence other members of their home.…”
Section: Discussionsupporting
confidence: 61%
“…4,5,18 COVID-19 vaccine hesitancy across Liberia and several countries in Africa was found to be associated with misinformation, lack of knowledge on COVID-19 transmission, concerns and fear about side effects, lack of trust in the vaccine, barriers to access and distrust of government. [6][7][8][9][10]16 Forty-two percent of households in this study had discordant views on the vaccine. A study by Schmaling, 2020 found that approximately 16 percent of couples had discordant COVID-19 vaccination status.…”
Section: Discussionmentioning
confidence: 99%
“…Beliefs about the attitudes and norms prevalent in one's social circle have been shown to influence individual attitudes and behavior. 23,24 Notably, people are found to often misperceive the true attitudes of those around them and correcting these beliefs can change behavior. 23 We explore community beliefs on vaccinations by asking respondents to estimate how many members of their community out of ten would be willing to be vaccinated.…”
Section: The Social Context Informs Vaccine Attitudesmentioning
confidence: 99%
“…28 Furthermore, a continuation of communication campaigns about the ongoing risk of COVID-19 and safety of vaccines will be pivotal: We find that the protection vaccines afford to one's own health is the main reason why people take up the vaccine and that hesitancy mostly relates to concerns about the vaccine's side effects. 24 As this was already the main concern among the hesitant in 2020 [14][15][16] , national vaccination campaigns should double-down on their efforts to assure the population of the safety of COVID-19 vaccines.…”
Section: Main Findings and Policy Recommendationsmentioning
confidence: 99%
“…For example, individuals in a variety of contexts value social acceptance by their neighbors and peers (Allcott 2011;Bond et al 2012;Gaube et al 2018;Gerber, Green, and Larimer 2008;Karing and Naguib 2021;Marshall 2019). These contexts include vaccination (Bicchieri et al 2021;Hoy, Kanagavel, and Cameron 2022;Karing 2019). Interventions that increase the social benefits of vaccination from vaccine-accepting neighbors and peers, including by increasing the information available about others' vaccination status (Alatas et al 2019;James et al 2021;Karing 2019;Karing and Naguib 2021;Moehring et al 2021), reminding individuals about familial and social impacts of vaccination (Clayton et al 2021;Rabb et al 2021;Ruggeri et al 2022;Tironi et al 2021), and sharing accurate vaccine information within social networks (Siddiqi et al 2020), may increase vaccination demand.…”
Section: Increasing the Social Benefits From Vaccinationmentioning
confidence: 99%